Antibiofilm and intraosteoblastic activities of rifamycins against Staphylococcus aureus: promising in vitro profile of rifabutin. (3rd March 2020) - Abad, Lélia; Josse, Jérôme; Tasse, Jason; Lustig, Sébastien; Ferry, Tristan; Diot, Alan; Laurent, Frédéric; Valour, Florent
Abstract: Background: Targeting biofilm-embedded and intraosteoblastic Staphylococcus aureus, rifampicin gained a pivotal role in bone and joint infection (BJI) treatment. Two other rifamycins, rifabutin and rifapentine, may represent better-tolerated alternatives, but their activity against bacterial reservoirs associated with BJI chronicity has never been evaluated. Objectives: To evaluate the activities of rifampicin, rifabutin and rifapentine in osteoblast infection models. Methods: Using three S. aureus isolates, rifamycins were compared regarding: (i) their intracellular activity in 'acute' (24 h) and 'chronic' (7 days) osteoblast infection models at 0.1× MIC, 1× MIC, 10× MIC and 100× MIC, while impacting infection-induced cytotoxicity (MTT assay), intracellular phenol-soluble modulin (PSM) secretion (RT–PCR), resistance selection and small colony variant (SCV) emergence; and (ii) their minimal biofilm eradication concentration (MBEC) and their MIC to prevent biofilm formation (bMIC). Results: At 0.1× MIC, only rifabutin significantly reduced intracellular inoculum and PSM secretion. All rifamycins allowed a 50% reduction of intraosteoblastic inoculum at higher concentrations, with no difference between acute and chronic infection models, while reducing infection-induced cytotoxicity and PSM secretion. Dose-dependent emergence of intracellular SCVs was observed for all molecules. No intracellular emergence of resistance was detected. bMICs were equivalent for all molecules, but MBEC90 s of rifapentine and rifabutin were 10- to 100-fold lower than those of rifampicin, respectively. Conclusions: All rifamycins are efficient in reducing the S. aureus intraosteoblastic reservoir while limiting infection-induced cytotoxicity, with a higher activity of rifabutin at low concentrations. All molecules prevent biofilm formation, but only rifapentine and rifabutin consistently reduce formed biofilm-embedded bacteria for all isolates. The activity of rifabutin at lower doses highlights its therapeutic potential.